A multiscale molecular dynamics allowing macroscale mechanical loads. (8th July 2015) - Tong, Qi; Li, Shaofan
Abstract: We proposed a novel multiscale molecular-dynamics model in order to apply macroscale boundary conditions to microscale molecular systems, which is difficult for classical molecular dynamics. Unlike in statistical mechanics, in which macroscale quantities such as temperature and pressure are collected from molecular information, the proposed approach is a reversed procedure to find optimal molecular states when macroscale conditions such as traction are enforced. The model is originated from Parrinello-Rahman molecular dynamics but extends it to solve finite-size, inhomogeneous molecular-dynamics problems by generalizing the representative volume element to a "material point" in continuum mechanics. An example of compressing a nickel nanowire is presented to demonstrate the capacity of the method to simulate localized phase transition in a finite-size molecular system, which validates the effectiveness of the method.